Uso de equipamentos de proteção individual entre enfermeiros em períodos distintos da pandemia de Covid-19 e fatores associados - Nogueira, Wynne Pereira (2023)
In the various covid-19 pandemic scenarios, health professionals played an indispensable role in controlling the pandemic, especially nurses, due to their workforce in caring for patients diagnosed with the infection. Given its direct and prolonged contact with the patient, the recommended use of Personal Protective Equipment (PPE) in direct assistance and in aerosol-generating procedures for patients suspected or diagnosed with Covid-19 was a significant measure to prevent the transmission of SARS -CoV-2 and the reduction in its contagion in the different phases of the pandemic. Therefore, the objective of this study was to analyze the use of PPE among nurses in different periods of the covid-19 pandemic and associated factors. This is a cross-sectional, analytical study, carried out with nurses from the state of Paraíba. Data collection took place at different periods of the pandemic, the first from October 1st to December 31st, 2020 and the second from November 1st, 2022 to May 1st, 2023. Nurses, at both times, were invited and recruited online through social networks. Data were collected through an online questionnaire, sent through a link that gave access to the SurveyMonkey® platform, in the first period of the research, and the REDCap platform, in the second period. Data were analyzed using descriptive statistics, Chi-Square test, logistic regression and Z test of proportion. All ethical precepts and standards established by Resolution No. 466/2012 were respected. In the first phase, 579 (100.0%) nurses from Paraíba participated, and in the second, 734 (100.0%). Nurses who provided care in a field hospital, who were diagnosed with covid-19 and who received sufficient and quality PPE were more likely to use PPE, while female nurses who did not receive a course and/or training on the disease presented reduced chances of use in direct assistance and in aerosol-generating procedures for patients suspected and/or diagnosed with Covid-19. In relation to the comparison of the combined use of PPE in different periods of the pandemic by nurses, in 2020, the percentage of use by nurses in direct assistance and in aerosol-generating procedures for patients suspected and/or diagnosed with covid-19 was higher when compared to the use in the year 2022. Therefore, health planning is necessary to protect nurses with the use of adequate and correct attire, within health environments, for patient safety and control epidemiology of covid-19.